2014
DOI: 10.1371/journal.pone.0097565
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin-A and Albumin Alter Cytotoxic Effects of Calcium Phosphate Nanoparticles on Human Vascular Smooth Muscle Cells

Abstract: Calcification is a detrimental process in vascular ageing and in diseases such as atherosclerosis and arthritis. In particular, small calcium phosphate (CaP) crystal deposits are associated with inflammation and atherosclerotic plaque de-stabilisation. We previously reported that CaP particles caused human vascular smooth muscle cell (VSMC) death and that serum reduced the toxic effects of the particles. Here, we found that the serum proteins fetuin-A and albumin (≥1 µM) reduced intracellular Ca2+ elevations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 43 publications
2
52
1
Order By: Relevance
“…At the same time, Na 3 Cit and Et 2 Cit effectively reduced cell damage. Dautova et al 14 found that nano-calcium phosphate crystals cause cell membrane damage, which can be effectively reduced after the addition of calcification inhibitors, such as Fetuin-A and albumin.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…At the same time, Na 3 Cit and Et 2 Cit effectively reduced cell damage. Dautova et al 14 found that nano-calcium phosphate crystals cause cell membrane damage, which can be effectively reduced after the addition of calcification inhibitors, such as Fetuin-A and albumin.…”
Section: Discussionmentioning
confidence: 99%
“…This condition leads to an imbalance in cell self-repair and steady-state mechanism, thereby leading to cell necrosis. 14,39 The addition of Na 3 Cit and Et 2 Cit could inhibit the increase in the intracellular Ca 2+ concentration induced by nano-HAp and lysosomal damage.…”
Section: +mentioning
confidence: 99%
See 3 more Smart Citations